Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap Turnover Intention Karyawan pada PT. Bumi Bara Prima Pekanbaru - Rachman, Muhammad Aditya; Rustam, Martha Hasanah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
This research was conducted at PT Bumi Bara Prima Pekanbaru. The purpose of this study was to determine the effect of job satisfaction and organizational commitment on employee turnover intention of PT Bumi Bara Prima Pekanbaru, both partially and simultaneously. The population in this study were 31 employees of PT Bumi Bara Prima Pekanbaru and the sample used in this study amounted to 31 people. The data used are primary data and secondary data. The data analysis method used is descriptive analysis method and quantitative analysis method. The results showed a regression value of 0.332 proving that Job Satisfaction partially had a positive effect on Turnover Intention. The effect of Organizational Commitment on turnover intention which states tcount 2.555> t table 1.996 and Sig 0.013 <0.05. This shows that Ha is accepted and Ho is rejected. This means that Organizational Commitment partially affects Turnover Intention at PT Bumi Bara Prima.